Equilibrium Wage Dispersion : An Example. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Search models with posting and match-specific heterogeneity generate wage dispersion. Given K values for the match-specific variable, it is known that there are K reservation wages that could be posted, but generically never more than two actually are posted in equilibrium. What is unknown is when we get two wages, and which wages are actually posted. For an example with K equal to 3, we show equilibrium is unique; may have one wage or two; and when there are two, the equilibrium can display any combination of posted reservation wages, depending on parameters. We also show how wages, profits, and unemployment depend on productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet